Congenital cerebral palsy with epilepsy: clinical and genetic comparisons - N. V. Chebanenko; P. L. Sokol; A. G. Prityko (Русский журнал детской неврологии, 2022)
Background. The problem of congenital cerebral palsy (CP) is relevant due to the limited complexity of habilitation and social adaptation of such patients. The genetic aspects of the pathogenesis of the disease are being actively studied. CP is often accompanied by epilepsy, which is characterized by refractoriness.Aim. To analyze the clinical, genetic and neuroimaging aspects of this pathology in CP patients.Materials and methods. The study included 136 patients with CP. Genetic studies were carried out on venous blood material using NGS and Sanger trio methods. The distribution of genes into groups of determinants was carried out.Results. In 136 patients, 91 genes with pathogenic variants were found. There were more of them in the determinant groups CS (regulation of cytoskeleton formation and functioning), ENM (regulation of neuronal membrane excitability), CMTR (control of chromatin modifications, transcription and replication processes), NTS (regulation of neurotransmitter metabolism and synapse functioning). The distribution of genes according to the degree of motor deficiency was specific: in all groups, except for canalopathy genes (ENM): certain genes corresponded to each degree of motor deficiency. This specificity was less pronounced in the ENM group. The largest number of cases of abnormalities in the structure of the brain was in the CMTR (control of chromatin modifications, transcription and replication processes), CS (regulation of the formation and functioning of the cytoskeleton) and ENM (regulation of the excitability of the neuronal membrane) groups. The RMF group (regulation of the functions of the mitochondrial apparatus) was characterized by the highest resistance to epilepsy. In cases from the group with the canalopathy genes (ENM), the epileptic process was not the most refractory.Conclusions. According to the contribution to the pathogenesis of CP with epilepsy, the distribution of determinants for the provision of excitability and conduction of the nervous tissue (ENM and NTS), the regulation of neuroontogenesis processes (NOG and CMTR), and the predetermination of enzymatic defects leading to storage diseases (GSD) are permissible. The determinant ENM is responsible for both the formation of motor deficits and the formation of the epileptic process. At the same time, its influence on motor deficit is nonspecific, and the degree of refractoriness of the epileptic process largely determines the determinant of mitochondrial function regulation.